Il lavoro oggi: fra informazione scientifica e discorso populista - Canal, Tiziana; De Minicis, Massimo (Cambio. Rivista sulle Trasformazioni Sociali, 2020)
Telling the work today, implies undeniably, to consider the relationship between production, science, technology and information society. In this context, How is the work told today? Who does it and how? This contribution attempts to answer these questions, narrowing the field of observation to the digital work of the Labor Platform, in relation to the ILO notion of decent work. It focuses, therefore, on the public discourse present in the scientific, political and information debate on digital work. In this context, the article, using Laclau’s interpretation on populism and in particular using his Theory of Speech, highlights as within what can be considered a distance between science, institutions and work can act a populist representation of the social identities of precarious work.